Teacher Strategies in Arabic Language Learning to Improve Student Motivation - Muhammad Saminu; Nabil Rosyadi; Silvia Ramadani; Azhar Jaafar (Journal of Arabic Literature, Teaching and Learning, 2025)
This study aims to analyze Arabic teaching strategies that can increase student motivation at the Islamic Junior High School level. The research method used is qualitative research with a case study approach, through classroom observation, interviews with teachers and students, and documentation of learning activities. The results of the study indicate that student learning motivation increases when teachers present interesting material, use varied learning methods, and utilize appropriate learning media. These strategies not only make the learning atmosphere more enjoyable, but also encourage students to actively engage in the Arabic language learning process. The implications of this study emphasize the importance of teacher innovation in designing materials, choosing methods that suit student characteristics, and optimizing the use of learning media to improve the quality of Arabic language learning in Islamic secondary schools.